Styl naukowy - JOLANTA NOCOŃ (Stylistyka)
The scientific variety of the Polish language is highly differentiated, which results from a broad definition of science as a sphere of human activity that is not only oriented towards the acquisition of new knowledge about the world, but also towards application, educational, and popularisation activities related to a range of contextual factors. Throughout the 20th century, numerous attempts were made to systematise its sub-varieties. While stylistic research in the 20th and 21st centuries has focused on specific problems and areas within the variety, there is a lack of synthetic and comprehensive studies. In the 20th century, scholars studied mainly stylistic features such as objectivity, logical coherence, precision, and abstractness, alongside their linguistic exponents (e.g. terminology, syntax and text structure of scientific texts, and genre conventions). The changing relationship between science and culture in the 21st century, however, has enabled Polish researchers to approach the scientific variety in a different way. A new type of “doing” science, departing from traditional approaches, has now been practiced in the humanities. The language of science has become less formalised, more figurative, and marked by rhetorisation and metaphorisation. Scholarly interest in it stems also from the domination of communication by pop culture and the Internet, and such processes as the mediatisation of science, the erosion of clear boundaries between the scientific and other varieties of Polish, the rise of edutainment, and what may be termed democratization of scientific discourse.